#TITLE_ALTERNATIVE# - (NIM 124 02 004) , Andriansyah
Abstract: Magnetotellurics (MT) data were acquired across southern part of DIY Yogyakarta by Research Center for Geotechnology -LIPI in collaboration with Hokkaido University and Tokyo Institute of Technology. This survey was related with 27 May 2006 earthquake in this area. The data were acquired at two lines (36 sounding sites), each line consists of AMT (audio frequency magnetotellurics) sites and AMT plus MT sites. The digital time series collected during the survey were processed by applying the robust estimation and remote reference method. The results are complex impedance tensor describing sub-surface resistivity distribution. MT data modeling produces geo-electrical section which imaged some dominant features, i.e. resistive basement (100-10000 myu m) interpreted as limestone. This basement has depth variations along the survey line, the shallowest basement is about 500 meters and the deepest is 2 kilometers. The basinal structure is filled with conductive materials (less than100 myu m) interpreted as sediment of young deposits of volcanic rock. The form of the basin indicates a structural break in the basement that can be associates with the Opak fault. The thick young sediment coincides with the severely damaged zone around Bantul. This thick young sediment is also confirmed by gravity data, i.e. low anomalies. Therefore, it can be concluded that severe damage in this area is due to amplification of earthquake wave in unconsolidated sediments.